Indian Economic Policy and Development - Bauer, P. T. (New York : Praeger, 1961)
This essay is largely revised and enlarged version of a study published under the title United States Aid and Indian Economic Development by the American Enterprise Association of Washington D.C. in 1959.
"Revised and enlarged version of ... United States aid and Indian economic development."
Includes bibliographical footnotes and index.
hza 28/06/2018
Loans
Keywords: Economic assistance, American; Technical assistance, American; India